EVALUASI KESETIMBANGAN KELARUTAN GAS KARBON DIOKSIDA (CO2) DALAM PELARUT ALKANOLAMINA MENGGUNAKAN SIMULATOR PROSES (Talenta Publisher (Universitas Sumatera Utara), 2015)
Acid gas removal to remove carbon dioxide (CO2) in natural gas is one of the most important processes. The common removal process of CO2 from natural gas by using alkanolamine solution This process was adopted as basic module in commercial process simulation tools with various equilibrium models. Thus, this study was focused to evaluate the validity in certain operating condition and equilibrium model that produced by commercial simulation tools. The model in this study included coefficient activity model based on Kent-Eisenberg, Li-Mather, and Electrolyte Non Random Two Liquid (NRTL). The evaluation was conducted by doing analysis from simulation result and experiment data that have been used as reference. Furthermore, validation test in absorption process simulation was done to compare column temperature profile. The overall conclusions show that electrolyte NRTL gives the most accurate result.